Vascular disrupting agents in clinical development - Hinnen, P (Nature Publishing Group, 2007)
Growth of human tumours depends on the supply of oxygen and nutrients via the surrounding vasculature. Therefore tumour vasculature is an attractive target for anticancer therapy. Apart from angiogenesis inhibitors that compromise the formation of new blood vessels, a second class of specific anticancer drugs has been developed. These so-called vascular disrupting agents (VDAs) target the established tumour vasculature and cause an acute and pronounced shutdown of blood vessels resulting in an almost complete stop of blood flow, ultimately leading to selective tumour necrosis. As a number of VDAs are now being tested in clinical studies, we will discuss their mechanism of action and the results obtained in preclinical studies. Also data from clinical studies will be reviewed and some considerations with regard to the future development are given.